Main Activities of the European Network of Forensic Science Institutes at the Present Stage - N. V. Govorina; S. A. Kuz’min; A. I. Usov (Теория и практика судебной экспертизы, 2019)
The article provides an outline of key events involving the European Network of Forensic Science Institutes. A key aspect of ENFSI activities is participation in the implementation of the European Union Council plan to create an integrated European Forensic Science Area 2020. This work is based on the EU system of direct grants, usually issued for a two-year period. A number of batch themed grants is discussed. The results of the Board, Standing Committee and Working Group activities, as well as scientifc projects coordinated by the ENFSI are presented. The interaction of ENFSI with external partners, primarily with members of the International Forensic Strategic Alliance uniting all major expert networks is brieﬂy analyzed.